Kurikulum Merdeka: Implementation and Effect on Learning Loss in Chemistry Caused by Covid-19 Outbreak - Bahriah, Evi Sapinatul; Yunita, Luki; Sholihat, Rizqy Nur (FKIP Universitas Lampung, 2022)
This research aimed to analyze the phenomenon of learning loss and its revitalization in chemistry learning in an effort to support the independent learning curriculum and find out the implementation of merdeka belajar in schools. The sample of this research was 227 students and 17 high school chemistry teachers in the Bogor area which were determined by cluster random sampling. The method used is descriptive with a survey approach. The instruments used in this study consisted of: student and teacher questionnaires and documentation. The data analysis technique used is quantitative descriptive. The results of the study show that: 1) the implementation of merdeka belajar in high schools in the Bogor area is included in the independent changing and independent sharing categories. 2) the percentage of the average score of the results of the student questionnaire is 62.4% (enough) and the teacher's questionnaire is 72.7% (good). 3) Based on statistical tests, a significance value of 0.000 ≥ 0.05 is obtained. So it can be concluded that the implementation of merdeka belajar at senior high schools in the Bogor area did not have an effect on the phenomenon of student learning loss in chemistry subjects.Keywords: learning loss, merdeka belajar, learning chemistry.DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1916-1927